NLOS Signal Detection Based on Single Orthogonal Dual-Polarized GNSS Antenna. (13th April 2017) - Zhang, Ke; Li, Baiyu; Zhu, Xiangwei; Chen, Huaming; Sun, Guangfu
Abstract : Nowadays users have a high demand for the accuracy of position and velocity, but errors caused by non-line-of-sight (NLOS) signals cannot be removed effectively. Since the GNSS signal is right-hand circular polarized (RHCP), the axial ratio of the strong NLOS signal is larger than that of the Line-of-Sight (LOS) signal. Based on the difference of the axial ratio, a method for NLOS signal detection using single orthogonal dual-polarized antenna is proposed. The antenna has two channels to receive two orthogonal linear polarized components of the incoming signals. Parallel cross-cancellation is used to remove the LOS signal while maintaining most of the NLOS signals from the receiving signals. The residual NLOS signals are then detected by conventional GNSS digital processor in real time without any prior knowledge of their characteristics. The proposed method makes use of the polarization and spatial information and can detect long delay NLOS signal by miniature and inexpensive receiver GNSS. The effectiveness of the proposed method is confirmed by simulation data.